Analysis of Different Classifiers’ Performance After Applying Three Different Feature Selection Methods - Ghosh, Kasturi; Nandi, Susmita (International Journal of Computer Sciences and Engineering, 2025)
Feature selection (FS) is an important aspect of data mining. Now a days availability of information with hundreds of variables leads to high dimensional, irrelevant and redundant data. Thus FS techniques must be applied on the datasets before classification or rule generation. It basically aims at reducing the number of attributes by removing irrelevant or redundant ones, while trying to reduce computation time and improve performance of classifiers. In this paper three different FS methods are used, Correlation Based, Information Gain Based and Rough set Based FS method. A statistical analysis of three different classifier's performance is also done in order to provide a detailed view.